Bubble Gum, Bubble Gum - Wheeler, Lisa; 1963-; Huliska-Beith, Laura (New York, 2004)
After a variety of animals get stuck one by one in bubble gum melting in the road, they must survive encounters with a big blue truck and a burly black bear.
Megan Tingley books.
Keywords: Bubble gum; Fiction; Animals; Fiction; Stories in rhyme